A Survey of UML Tools - Weng, Jie Thong; M. A., Ameedeen (2015)

(untitled)
Unified Modeling Language (UML) is a modeling language widely used in the field of software engineering. It is a standard to visualize the design of a system structurally and behaviorally. UML tools are software tools used to create UML diagrams, perform model and diagram interchange, model transformation, code generation, reverse engineering and round-trip engineering, There are many free UML tools available to be downloaded in the internet. This paper serves as a survey for ten UML tools and gives recommendation to users on which UML tools to be used in different situations. The result of the survey is tabulated so that users are easily able to compare the ten UML tools based on the criteria set by the author.